2014
DOI: 10.7899/jce-14-16
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the change in attitudes, knowledge, and perspectives of medical students towards chiropractic after an educational intervention*

Abstract: Objective:We assessed the change in attitudes, knowledge, and perspectives of medical students towards chiropractic after a 1-hour educational intervention. Methods: A mixed-methods approach was used with a 52-item cross-sectional paper survey and 1 focus group of thirdyear medical students. The views of these medical students towards chiropractic were assessed previously in their second-year of medical school. ANOVA and the Wilcoxon rank-sum test were used to assess between-group differences between the medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Previous studies have considered medical/health care interns as having higher levels of self-confidence than actual knowledge in EBM. 7,12,13 This shows a level of self-confidence that did not correlate with that of clinical supervisors. This is consistent with internal assessment conducted at IMU and the chiropractic program regarding work preparedness.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have considered medical/health care interns as having higher levels of self-confidence than actual knowledge in EBM. 7,12,13 This shows a level of self-confidence that did not correlate with that of clinical supervisors. This is consistent with internal assessment conducted at IMU and the chiropractic program regarding work preparedness.…”
Section: Discussionmentioning
confidence: 86%
“…Over half of the respondents to the current survey wanted to know more about chiropractic care, which suggests a role for interprofessional education in this area. [42][43][44] Themes for education may include recent studies on safety and efficacy of chiropractic care, clinical training of chiropractors, 15 as well as strategies to improve documentation and sharing of clinical information. 45 Münstedt et al have suggested development of interprofessional working groups that focus on creating evidence-based resources such as clinical practice guidelines to help improve relationships between obstetricians and complementary and alternative medicine providers.…”
Section: Implications and Future Researchmentioning
confidence: 99%
“…[1][2][3][4][5] Although physicians, nurse practitioners (NPs), and physician assistants (PAs) display expanding interest and favorable perspectives toward integrative therapies, a lack of knowledge regarding treatment options, indications, and referral protocols presents a self-reported formidable barrier for implementation. [6][7][8][9][10][11][12][13] Integration of CAM, particularly in the area of chiropractic, into mainstream health care continues to lag in many countries despite the increasing amount of evidence regarding the safety, effectiveness, public interest, and cost-effectiveness of its use. 14 Improving integrative medical knowledge is prioritized by the World Health Organization's Traditional Medicine Strategy 2014-2023 as one of the primary objectives in improving health and integrating CAM into national health care systems.…”
Section: Introductionmentioning
confidence: 99%
“…1 In accordance with these principles, integrative medicine is now taught, practiced, and researched in nearly half the medical schools in the United States. 13 A recent study by Wong et al 13 showed that Canadian medical students increasingly view chiropractic as a sound evidence-based complementary therapy for low back/chronic pain; however, the students also reported a need for greater understanding of chiropractic for application in future patient referrals. While the results from Wong's study highlight the importance of integrating chiropractic education into mainstream medical education, the knowledge and attitudes of NPs and PAs in the area of CAM integration, particularly chiropractic, remains unclear.…”
Section: Introductionmentioning
confidence: 99%